2014
DOI: 10.1055/s-0033-1340482
|View full text |Cite
|
Sign up to set email alerts
|

Twists and Turns Around a Square: The Many Faces of Squaraine Chemistry

Abstract: The purpose of this account is to give an overview of the wide variety of available structures that share the common name 'squaraines', with particular attention to the results achieved by our group in the last ten years. The first section of the report is an introduction and a description of the motivation for our interest in squaraine compounds. The second section includes a survey of the history of squaraines in the scientific literature, and the third section contains a general description of their synthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 95 publications
0
48
0
Order By: Relevance
“…Functional dyes have been widely investigated as molecular semiconductors in (opto)electronic devices, owing to their intense absorption and high quantum yield fluorescence emission at low energies . Among these materials, squaraine dyes have been the subject of many studies because of their remarkable donor–acceptor–donor (D–A–D) type structure, enabling systems with very small optical band gaps, and ultimately, unique photochemical/photophysical properties . Applications include organic solar cells, nonlinear optics, photodetectors, light‐emitting/ambipolar field‐effect transistors (FETs), and fluorescent labels/sensors for a wide range of analytes .…”
Section: Introductionmentioning
confidence: 99%
“…Functional dyes have been widely investigated as molecular semiconductors in (opto)electronic devices, owing to their intense absorption and high quantum yield fluorescence emission at low energies . Among these materials, squaraine dyes have been the subject of many studies because of their remarkable donor–acceptor–donor (D–A–D) type structure, enabling systems with very small optical band gaps, and ultimately, unique photochemical/photophysical properties . Applications include organic solar cells, nonlinear optics, photodetectors, light‐emitting/ambipolar field‐effect transistors (FETs), and fluorescent labels/sensors for a wide range of analytes .…”
Section: Introductionmentioning
confidence: 99%
“…A detailed description of all of the precise squaraine variants can be found in [82]. The first published review of squaraine chemistry was reported later that same year by Maahs and Hegenberg [71], which included a section on pyrrolyl squaraines.…”
Section: The Beginning: the First Three Yearsmentioning
confidence: 99%
“…Additionally increasing throughout this period of time was the synthesis of unsymmetrical pyrrole squaraine dyes [19,39,48,53,57,69,70]. Although a synthetic route to the pyrrole half-squaraine, semisquaraine, or emisquaraine (the necessary precursor to an unsymmetrical pyrrole squaraine dye), was first proposed in 1968 [3], more efficient (and safer) routes have been developed in recent times (refer to [82] for a good description and schematics). Mention should also be added on the increase in recent years in the synthesis of (what in [82] is referred to as) core substituted squaraines, although only one example of this type of squaraine is known in a pyrrole squaraine [53].…”
Section: The Pyrrolyl Squaraine Explosion: 2001-currentmentioning
confidence: 99%
See 1 more Smart Citation
“…[32,[42][43][44][45][46][47][48][49][50][51][52][53][54][55] In particular, we considered one of the simplest squaraine structures -the anilino-squaraines -to demonstrate the method (thereby providing proof of concept data) rather than focusing at this juncture on attaining particularly high conversion efficiencies. The choice of squaraines (the 1,3-dicondensation products of squaric acid and two equivalents of electron rich precursors) among all possible donor materials described in the literature is due to the fact that such compounds offer a good trade off between synthetic accessibility and overall conversion efficiencies.…”
Section: Introductionmentioning
confidence: 99%